1969
DOI: 10.1111/j.1749-6632.1969.tb15851.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Delayed Neurotoxicity Produced by Some Organophosphorus Compounds

Abstract: It has been known for over 30 years (Smith & Elvove, 1930) that tri 2-methylphenylphosphate produces in man and the hen a delayed neurotoxicity characterized by ataxia and weakness of the limbs. For the purposes of this p ' ! y r , we will discuss the clinical condition in hens that appears 8 to I 4 days after dosing and from which there is little or no recovery within 2 months in birds cver 9 months of age. We exclude from this discussion the acute cholinergic response to some compounds and also the condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

1975
1975
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…Organophosphates exhibit behavioral, neurological, and biochemical effects in both animals and humans (Holmstedt, 1959; Davis and Richardson, 1980). On long‐term exposure, these compounds are known to induce neurotoxic effects (Aldridge et al, 1969; Johnson, 1975; 1977). Tolerance develops to the behavioral effects of these agents and evidence suggests that this may result from subsensitivity to acetylcholine (ACh) (Russell et al, 1969; 1981).…”
mentioning
confidence: 99%
“…Organophosphates exhibit behavioral, neurological, and biochemical effects in both animals and humans (Holmstedt, 1959; Davis and Richardson, 1980). On long‐term exposure, these compounds are known to induce neurotoxic effects (Aldridge et al, 1969; Johnson, 1975; 1977). Tolerance develops to the behavioral effects of these agents and evidence suggests that this may result from subsensitivity to acetylcholine (ACh) (Russell et al, 1969; 1981).…”
mentioning
confidence: 99%
“…It has also been shown that only that a negligible proportion of soman-inhibited NTE from hen brain and spinal cord undergoes the ageing reaction believed to be an essential preliminary to the development of OPIDP. Additionally, structure-activity considerations would not lead one to expect nerve agents to be neuropathic (Aldridge et al, 1969). Thus, soman demonstrably lacks neuropathic potential.…”
Section: Opidpmentioning
confidence: 98%
“…The phosphate group of the OPs is highly reactive [22] and Schulman has recently reviewed the importance of phosphorylation in neuronal plasticity and gene expression [23]. Active phosphate group donors, therefore, would seem highly likely to have profound deranging influences on these important processes.…”
Section: Neurochemical Studiesmentioning
confidence: 99%